Perbandingan Pelaksanaan Pelayanan Kolaborasi Masa Nifas terhadap Kejadian Postpartum Blues di Puskesmas Sewon I & Banguntapan II Kabupaten Bantul Tahun 2020 - Dessy Hertati; Detty Siti Nurdiati; Sulistyaningsih Sulistyaningsih; Djaswadi Dasuki (Jurnal Surya Medika (JSM), 2022)
Postpartum blues is a mild mood disorder syndrome often ignored by postpartum mothers, families, or health workers. Postpartum blues can develop into depression and even psychosis. The incidence varies significantly in Asia, between 26-85%, whereas the incidence is around 50-70% in Indonesia. Postpartum blues also affect the interaction between the baby and the mother, especially during the first year. In mental health, collaborative practice can increase patient and health team satisfaction, reduce the duration of treatment, reduce the cost of care, reduce the incidence of suicide, and reduce outpatient visits. The study aimed to analyze the differences between the implementation of postpartum collaboration services and postpartum blues at Sewon I & Banguntapan II Primary Health Center of Bantul Regency in 2019. This study applied a comparative study with a prospective cohort approach, and the sampling technique used consecutive sampling. Data analysis employed the Wilcoxon test, Mann-Whitney, and binary regression. Wilcoxon test p=0,000 means a difference in the initial and final EPDS score reduction between the two Primary Health Centers and the postpartum blues incidence. The number of postpartum blues in Sewon I Primary Health Center reached 52 (44.83%), while in Banguntapan II, there were 45 (42.45%). Fisher exact test results pregnancy relationship p = 0.642 and history of depression p = 0.078 meaning that there was no relationship. The binary regression test of the age obtained p = 0.000 and parity p = 0.007, meaning a relationship. It can be concluded that Inter-professional Collaboration has become an effective and efficient strategy to improve the quality of services and patient health outcomes due to the increasing diversity of professions in the health sector and the increasingly complex patient problems.